Voluntary Wheel Running Reverses Deficits in Social Behavior Induced by Chronic Social Defeat Stress in Mice: Involvement of the Dopamine System - Zhang, Jing; He, Zhi-xiong; Wang, Li-min; Yuan, Wei; Li, Lai-fu; Hou, Wen-juan; Yang, Yang; Guo, Qian-qian; Zhang, Xue-ni; Cai, Wen-qi; An, Shu-cheng; Tai, Fa-dao (Frontiers in Neuroscience, 2019)
Voluntary exercise has been reported to have a therapeutic effect on many psychiatric disorders and social stress is known to impair social interaction. However, whether voluntary exercise could reverse deficits in social behaviors induced by chronic social defeat stress (CSDS) and the underlying mechanism remain unclear. The present study shows that CSDS impaired social preference and induced social interaction deficiency in susceptible mice. Voluntary wheel running (VWR) reversed these effects. In addition, CSDS decreased the levels of tyrosine hydroxylase in the ventral tegmental area and the D2 receptor (D2R) in the nucleus accumbens (NAc) shell. These changes can be recovered by VWR. Furthermore, the recovery effect of VWR on deficits in social behaviors in CSDS mice was blocked by the microinjection of the D2R antagonist raclopride into the NAc shell. Thus, these results suggest that the mechanism underlying CSDS-induced social interaction disorder might be caused by an alteration of the dopamine system. VWR may be a novel means to treat CSDS-induced deficits in social behaviors via modifying the dopamine system.